2005
DOI: 10.1074/jbc.m500940200
|View full text |Cite
|
Sign up to set email alerts
|

The Stomatin/Prohibitin/Flotillin/HflK/C Domain of Flotillin-1 Contains Distinct Sequences That Direct Plasma Membrane Localization and Protein Interactions in 3T3-L1 Adipocytes

Abstract: Flotillin-1 is a lipid raft-associated protein that has been implicated in various cellular processes. We examined the subcellular distribution of flotillin-1 in different cell types and found that localization is cell type-specific. Flotillin-1 relocates from a cytoplasmic compartment to the plasma membrane upon the differentiation of 3T3-L1 adipocytes. To delineate the structural determinants necessary for its localization, we generated a series of truncation mutants of flotillin-1. Wild type flotillin-1 has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
123
2
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(137 citation statements)
references
References 42 publications
8
123
2
4
Order By: Relevance
“…1), suggesting the maintenance of an important function in both types of structural element. Recent reports suggest that reggies/flotillins interact with F-actin [9], and that small and hydrophobic residues within a helices from actin-binding proteins are likely to interact with actin [34]. We analyzed the a helices within .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1), suggesting the maintenance of an important function in both types of structural element. Recent reports suggest that reggies/flotillins interact with F-actin [9], and that small and hydrophobic residues within a helices from actin-binding proteins are likely to interact with actin [34]. We analyzed the a helices within .…”
Section: Resultsmentioning
confidence: 99%
“…Although they were initially thought to be components of caveolae [4], subsequent biochemical and microscopic characterization revealed that these 48-kDa proteins are distinctive non-caveolar markers of detergent-resistant microdomains (DRMs) [3,6]. In humans, reggie-1 and reggie-2 polypeptides show similar length, primary sequence composition and biochemical profiles, with a conserved protein architecture at the N terminus containing one myristoylation site (Gly-2, only in reggie-1) and four palmitoylation sites (Cys-5, Cys-19, Cys-20, Cys-38), which are thought to assist in membrane association and lipid raft targeting [7][8][9]. Reggies/flotillins do not have typical transmembrane domains, but harbor two conserved hydrophobic stretches that allow potential interactions with the inner leaflet of the plasma membrane, and possibly protein-protein interactions [7,8].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, ␤1-integrin recruitment can lead to an activation of Rac1 in HeLa cells (O'Toole et al, 2011). Since reggies interact with Rab11a and Src (Liu et al, 2005;Solis et al, 2012;Stuermer et al, 2001Stuermer et al, , 2004 it is possible that reggies at vesicles and at the plasma membrane coordinate the interactions, underlying FA formation and turnover. Or FAK activation is caused by defective integrin recycling in consequence of loss of reggie-1 or both.…”
Section: Influence Of Reggie On Fak Rac1 and Rab11 Activationmentioning
confidence: 99%